Association of Elevated Pre-Operative Cardiac Troponin I Levels with Post Operative Outcome After Coronary Artery Bypass Grafting at Peshawar Institute of Cardiology (Medical Forum Monthly, 2023)
Objective: To find out the role of pre-operative cardiac Troponin I level with post operative outcome following a Coronary Artery Bypass Grafting (CABG).Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Cardiac Surgery at MTI-Peshawar Institute of Cardiology (PIC). Duration: March 2022 to February 2023.Materials and Methods: Selection of subjects was done according to the inclusion and exclusion criteria. They were divided into two cohorts. Acute MI patients with raised pre-CABG troponin I (Group A N=64) and a second group with normal pre operative troponin I (Group B N=59). Post operative outcome was assessed in terms of post operative (CABG) chest pain and hospital stay. The data was analysed using SPSS version 26.0 for MacBook Pro and organised as tables.Results: Troponin I level showed statistical difference (p<0.05) for both groups, with higher values for group A (5.14 ng/mL ± 2.16ng/mL) in comparison with group B (0.09 ng/mL ± 0.06ng/mL) subjects. Group A subjects had a prolonged hospital stay (10 days ± 2 days) and higher post operative (CABG) chest pain for longer periods of time in comparison to group B (5 days ± 1 day) and lower post operative pain.Conclusion: In conclusion, this study found a direct relation between raised pre operative troponin levels and post CABG complications (hospital stay and post operative chest pain). This makes cardiac troponin I not only a diagnostic but a relatively fair and good marker or prognosis in assessing post CABG outcomes. The raised Troponin I in group A are associated with the post CABG outcomes.